2008
DOI: 10.4137/bmi.s564
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Biomarkers of Human Breast Milk Pollution

Abstract: Human milk is, without question, the best source of nutrition for infants containing the optimal balance of fats, carbohydrates and proteins for developing babies. Breastfeeding provides a range of benefi ts for growth, immunity and development building a powerful bond between mother and her child. Recognition of the manifold benefi ts of breast milk has led to the adoption of breast-feeding policies by numerous health and professional organizations such as the World Health Organization and American Academy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Some studies found that Cd levels in human milk were significantly related to mothers’ smoking status [10] and have even found that there was a direct relation between the amount of cadmium in a woman’s breast milk and the number of cigarettes she smoked a day [10, 31, 32]. A study from Austria showed that smokers had 2-times higher concentration of cadmium than non-smokers [3].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that Cd levels in human milk were significantly related to mothers’ smoking status [10] and have even found that there was a direct relation between the amount of cadmium in a woman’s breast milk and the number of cigarettes she smoked a day [10, 31, 32]. A study from Austria showed that smokers had 2-times higher concentration of cadmium than non-smokers [3].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the frequency and mean concentration of AFM1 in breast milk samples vary in different countries, indicating that the contamination rate is lower in the developed countries compared to that in developing/undeveloped countries. Studies from Germany, France, and England reported no contamination in breast milk samples 19 , 20 . However, the results of a study in Australia showed that 26% of the milk samples of 73 lactating women were contaminated with AFM1, which can be attributed to the warm and humid climate of this country [21] .…”
Section: Discussionmentioning
confidence: 95%
“…63,64 Data show the significant concentrations of dioxins in milk of Eskimos, Japanese, and Italian women who breastfed are several times higher than the permissible for an adult. 65 The dioxin content in the bodies of polar bears and their milk is comparable to the concentrations of these compounds in seals, which are their food source as well as the Eskimo milk. 66,67 All these prove the bioaccumulation and the circulation of dioxin in the food chain.…”
Section: Dioxin Accumulation and Its Impact On Orofacial Clefts Develmentioning
confidence: 99%